THE IMPACT OF SOY ON CANCER RISK AND OUTCOMES - Stanisław Ciechanowicz; Julia Ciechanowicz; Julia Dura; Marika Gutowska; Piotr Kupidłowski; Agata Nowacka; Adrianna Perzanowska; Aleksandra Przybylska; Zuzanna Tomaszewska; Anna Zielińska (International Journal of Innovative Technologies in Social Science, 2025)
Aim: Soy consumption is growing globally, bringing attention to its health effects. This review aims to summarize current knowledge about the impact of soy on the risk and outcomes of various cancers. Methods: The study is based on meta-analysis, randomized controlled trials, and systematic reviews from the PubMed database published over the past 15 years. Key findings and Conclusions: Existing literature indicates significant health benefits associated with soy intake in the prevention of breast and prostate cancer. Studies provide moderate to weak evidence for an inverse association between soy intake and the risk of gastric, gastrointestinal, colorectal, endometrial and lung cancers. No significant relationship has been identified between soy supplementation and the risk of ovarian cancer, bladder cancer and leukemia. The exact mechanisms responsible for the anticancer properties of soy remain unknow and available research is characterized by high heterogeneity. Therefore, there is a need for larger studies concentrating on specific soy compounds.